Transcranial management of pituitary tumours with suprasellar extension. - Symon, L (1979)
A consecutive series of 101 pituitary tumours treated in the 10 year period 1968-78 has been examined, giant lesions being excluded. There were 48 female cases and 53 male, women predominating in the ratio of three to two in the age group 40-50 years and men showing a slight predominance in the age group 50-60 years. Most cases presented with visual deterioration which in 22 cases had been present for between one and two years, and in a further 22 for an even longer period, between two and 10 years. All patients underwent subfrontal craniotomy with mainly radical excision of the tumour followed by radiotherapy. The operative mortality was 0.99%. A system of grading of visual field defect has been described and used to compare preoperatively visual loss with postoperative visual recovery. Fifty-six per cent of cases returned to normal vision over the first two years, and a further 37% showed appreciable improvement in visual fields or acuity or both. Six per cent of cases showed no improvement in visual fields, and one patient died of postoperative deep vein thrombosis and pulmonary embolism. The degree of visual improvement has been correlated with the extent of visual defect, length of visual complaint, and size of the tumour. The importance of central and peripheral visual field analysis is emphasised yet again.